Analysis of Criminal Liability and Determining Factors in Medical Malpractice Cases - Bardaeni, Bardaeni; Sudarto, Sudarto (Neolectura, 2025)
Medical malpractice is a form of action carried out by health experts, namely doctors, who in carrying out their obligations deviate from what they should be. If the action taken causes physical or material harm to others, in this case the patient, the deviant action can be held accountable either criminally, civilly, or administratively. The research method used is normative juridical. The results of the study are Criminal liability for medical malpractice in Law Number 17 of 2023 concerning Health, namely that the laws and regulations in Indonesia basically do not explicitly regulate criminal liability for malpractice. Provisions regarding criminal liability for Malpractice in Article 447 paragraph (1) of Law No. 17 of 2023 concerning Health. The determining factors in medical malpractice cases are Professional Standards and Operational Procedures; Doctor-Patient Relationship; Negligence and Elements of Professional Error; Evidence of Losses and Causal Relationship; Competence and Experience of Medical Personnel; Role of Technology and Health Facilities; and Legal Supervision and Regulation System. From the perspective of legal certainty and justice, legal certainty provides a clear and objective basis for resolving cases, while justice ensures that all parties receive balanced treatment and no one is harmed unilaterally. The combination of the two is the key to creating a more accountable and humane health system.